Virtual Machine based Autonomous Web Server - Mas’ud, M. Z.; Abdollah, M. F.; Yaacub, A. H.; Ahmad, N. M.; Abdul Hamid, E. (2011)
Enterprises are turning to Internet technology to circulate information, interact with potential customers and establish an e-commerce business presence. These activities are depending highly on Web server and maintaining good server security has been a requirement for avoiding any malicious attacks especially web defacements and malware. Web server administrators should be alert and attentive to the status of the server at all time. They need to be persistent in monitoring the server in order to detect any attempted attacks. This is an advantage for a web server that is maintained by a big company that has a big budget to hire a knowledgeable web server administrator, for a new established small company it will only burden their expenses. To overcome this problem, this paper proposes a low cost system called Autonomous Web Server Administrator (AWSA) that is fully developed using open source software. AWSA combines several computing concepts such as Virtual Machine, Intrusion Detection System and Checksum. AWSA offers a Virtual Machine based Web server that has the ability to automatically detect intrusions and reconstruct corrupted data or the file system without any human intervention.